Dysfunctional Lens Index Serves as a Novel Surgery Decision-Maker for Age-Related Nuclear Cataracts. (3rd July 2019) - Li, Zhangliang; Yu, Liuqing; Chen, Ding; Chang, Pingjun; Wang, Dandan; Zhao, Yinying; Liu, Songjia; Zhao, Yun-E
ABSTRACT: Purpose : To study the correlations between subjective and objective cataract metrics with dysfunctional lens index. To investigate the potential of the DLI as a novel surgery decision-maker. Methods : In this prospective, cross-sectional study, we measured the dysfunctional lens index (DLI), Lens Opacities Classification System III nuclear opalescence (LOCS III NO) grading, preoperative corrected distance visual acuity (CDVA), objective scatter index (OSI) and Scheimpflug-based average lens density (ALD) in eyes with nuclear cataract. Eyes were classified as Surgical and Non-Surgical groups. Correlations among the DLI, OSI, ALD, LOCS III NO grading, and preoperative CDVA were analyzed. The receiver operating characteristic (ROC) curve analysis was performed for DLI, OSI, and CDVA to determine optimal cut-off values to separate between surgical and non-surgical cataracts. Results : The DLI showed the strongest correlation with the OSI ( r = −0.712, P < .001), followed by LOCS III NO score ( r = −0.661, P < .001), ALD ( r = −0.596, P < .001) and preoperative CDVA ( r = 0.563, P < .001). The area under ROC curves (AUCs) of the DLI, OSI and preoperative CDVA curve were 0.972, 0.912 and 0.844 (All P < .001), respectively. The DLI cut-off value of 5.7 implied higher levels of sensitivity (91.67%) and specificity (91.84%) than the OSI cut-off value of 2.9 and the CDVA cut-off value of 0.55 (sensitivity of 89.58% and 71.92%; specificity of 81.63% and 85.71%, respectively). Conclusion : The surgery criterion of DLI ≤ 5.7 behaved better than the surgery criterions of OSI ≥ 2.9 and preoperative CDVA ≤ 0.55 in discrimination between surgical and non-surgical nuclear cataracts.